TRANSFORMASI FISIK WILAYAH PERI URBAN DI KELURAHAN MADEGONDO KECAMATAN GROGOL KABUPATEN SUKOHARJO - Wildani Miftahul Fauzan; Soedwiwahjono Soedwiwahjono; Nur Miladan (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2017)
The peri-urban area is a strategic area to support the surrounding city needs. The increasing lack of urban areas makes peri-urban areas a potential new destination for city development, because of lower peri-urban land prices, large land reserves, and ease of access to a nearby city. Kelurahan Madegondo (The Administrative Village of Madegondo) is a peri-urban area directly adjacent to the Southern part of Surakarta. Defined as an administrative village, this area has developed and transformed to be a more of an urban area. This research focus on identifying transformations happened in Madegondo in the period of 15 years, specifically from 2002 to 2017. Using Geographic Information System (GIS) and System for Automated Geoscientific Analyses (SAGA) in the process. This study has identified many crucial transformations occurred in Madegondo. Major land-use change has occurred in the period of 15 years, 54 hectares of non-covered land has itself covered with buildings. Building density has shifted in 15 years from mid-density (40,82%) to very high-density (78,39%). Another change identified is circulation transformation, which characteristics have grown to be more complex in 2017.